The effect of static magnetic field on solid–liquid interfacial free energy of Al–Cu alloy system. (October 2020) - Huang, Chenglin; Shuai, Sansan; Wang, Pengchuan; Liu, Xin; Wang, Jiang; Ren, Zhongming
Abstract: The effect of static magnetic field (SMF) on the solid–liquid interfacial free energy of Al–Cu alloy system was experimentally determined by an improved grain boundary groove method. The value of the solid α-Al-liquid Al–Cu system was found to increase from (157.16±14.14) × 10 −3 Jm −2 to (206.65±18.60) × 10 −3 Jm −2, with an increasing rate of 31.5%, while that of the solid CuAl2 -liquid Al–Cu system decreased by 46.17% from (280.70±25.26) × 10 −3 Jm −2 to (151.11±13.56) × 10 −3 Jm −2 with SMF. The influence of SMF on the value of Al-Cu alloy system was explained as the formation of magnetic dipole on the solid-liquid interface, which was supposed to change the surface tension. Graphical abstract: Image, graphical abstract